Penerapan Media Pembelajaran Berbasis Digital Pada Mata Pelajaran IPA di SD Negeri 060877 Medan Perjuangan - Endina Dwiva Perbina Br Tarigan; Mutiara Gultom; Sri Lewi Giovani Lubis; Khairunnisa Khairunnisa (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to apply digital learning media to science subjects in elementary school, animal life cycle material for 4th grade elementary school students. Research design using the R&D model according to Borg and Gall includes initial research and data collection, product planning, initial product format development, initial trials, product revisions, main field trials, product revisions, operational field trials, and product refinement. Research subjects included validation tests by material experts and media experts, and field trials(25 students), involving grade 4 students at UPT SD Negeri 060877 Medan Perjuangan. Data collection techniques use questionnaires or questionnaires. The data type is quantitative descriptive. The results of this research received a material expert assessment in the very good category